A universal gene expression system for fungi. Issue 18 (19th June 2018) - Rantasalo, Anssi; Landowski, Christopher P; Kuivanen, Joosu; Korppoo, Annakarin; Reuter, Lauri; Koivistoinen, Outi; Valkonen, Mari; Penttilä, Merja; Jäntti, Jussi; Mojzita, Dominik
Abstract: Biotechnological production of fuels, chemicals and proteins is dependent on efficient production systems, typically genetically engineered microorganisms. New genome editing methods are making it increasingly easy to introduce new genes and functionalities in a broad range of organisms. However, engineering of all these organisms is hampered by the lack of suitable gene expression tools. Here, we describe a synthetic expression system (SES) that is functional in a broad spectrum of fungal species without the need for host-dependent optimization. The SES consists of two expression cassettes, the first providing a weak, but constitutive level of a synthetic transcription factor (sTF), and the second enabling strong, at will tunable expression of the target gene via an sTF-dependent promoter. We validated the SES functionality in six yeast and two filamentous fungi species in which high (levels beyond organism-specific promoters) as well as adjustable expression levels of heterologous and native genes was demonstrated. The SES is an unprecedentedly broadly functional gene expression regulation method that enables significantly improved engineering of fungi. Importantly, the SES system makes it possible to take in use novel eukaryotic microbes for basic research and various biotechnological applications.